Lecturers and normative ethical theories: A survey of UiTM lecturers / Sharifah Norhafiza Syed Ibrahim - Syed Ibrahim, Sharifah Norhafiza (2003)
This paper intends to discuss several normative ethical theories, namely teleological (consequences) and deontological (duties) theories and to find out how these theories apply to the teaching staff in UiTM Kampus Jengka. The former theories state the right decision is the one that produces the greatest benefits to the greatest number of people. The latter theories determine right or wrong decision or action by looking at the intention of the particular act. A questionnaire contains five questions and six statements was used. The questionnaires were distributed to half of the total population; a hundred and forty lecturers were selected at random. Only one third of the respondents successfully completed and returned the questionnaires. Statistical Package for Social Science was used to analyse the responses. Simple descriptive tables were used in the data analysis. This survey found out that majority of respondents (71 %) gave the most accurate definition of ethics. About sixty-five percent of the total respondents follow deontological theories. This suggests that more lecturers put higher considerations to the good intention in making the right decision. This is supported by the other findings that show many respondents agree to obey moral values such as not to deceive people, not to lie and to keep promises at all times. Besides, many respondents agree that we should respect the right of others. Furthermore, almost all respondents think that the employer should not interfere into his/her employees' private life and everybody should be treated equally except if he/she deserves differently.